Pengaruh Digitalisasi Proses SDM terhadap Efisiensi Rekrutmen dan Pelatihan di Industri Tekstil - Erry Cahyono (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Digitalization of human resource (HR) processes has emerged as a strategic imperative for the textile industry, driven by the need to enhance operational efficiency and sustain competitive advantage. This study investigates the impact of Electronic Human Resource Management (E-HRM) on recruitment efficiency and Learning Management Systems (LMS) on training effectiveness in textile manufacturing firms. Drawing upon empirical evidence from quantitative and descriptive-empirical studies conducted between 2018 and 2024, data were synthesized to evaluate key performance metrics before and after digital adoption. Regression analyses indicate that six core E-HRM practices e-job analysis, e-recruitment & selection, e-compensation & benefits, HRIS & e-communication, e-personal profiles, and e-performance appraisal collectively explain 67% of the variance in operational efficiency for recruitment processes. LMS implementation produced a 40% average increase in workforce productivity, a 50% reduction in training costs, and a 60% acceleration in onboarding time. The integration of E-HRM and LMS fosters an end-to-end HR value chain, enabling seamless transition from candidate acquisition to tailored learning pathways. Despite substantial benefits, barriers such as legacy system integration, data security concerns, digital literacy gaps, and organizational resistance pose challenges to widespread adoption. Practical recommendations include strengthening IT infrastructure, deploying robust change management strategies, and instituting digital literacy programs. Policymakers and industry associations should provide targeted incentives and guidelines to support small and medium textile enterprises in their HR digital transformation journey. The findings offer actionable insights for textile firms seeking to design comprehensive roadmaps for digital HR, thereby optimizing recruitment and training outcomes in the era of Industry 4.0.